2016
DOI: 10.4103/0976-5042.195725
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of yield of endoscopic ultrasonography in the etiological diagnosis of "idiopathic" acute pancreatitis

Abstract: Background: Etiology of acute pancreatitis (AP) remains idiopathic in 30% of patients. Endoscopic ultrasound (EUS) has been shown to increase the diagnostic yield in patients with idiopathic AP (IAP). Aim: The aim of this study was to evaluate the role of EUS in achieving etiological diagnosis in patients with IAP. Materials and Methods: Consecutive 192 patients with IAP were evaluated prospectively with EUS over a period of 2 years. Patients who had no etiological diagnosis for AP after detailed history, clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
1
0
1
Order By: Relevance
“…Moreover, 67 patients were below 40 years of age while 42 patients were above 40 years of age with good significance (P=0.01). It shows idiopathic acute pancreatitis is more common in young age which is consistent with previous studies (Elzouki et al, 2019).In foregone studies, among the patients of idiopathic acute pancreatitis about 20-50% presented with microlithiasis (Liu et al, 2000;Ros et al, 1991;Dill & Dill, 2002;Lee & Nicholls, 1986;Levy, 2002) , 15% with chronic pancreatitis (Wilcox & Kilgore, 2009), 25% with common bile duct stone (Choudhary et al, 2016) and about 3.2% with pancreatic cancer (Tandon & Topazian, 2001). Our study almost resembled those previously found data.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Moreover, 67 patients were below 40 years of age while 42 patients were above 40 years of age with good significance (P=0.01). It shows idiopathic acute pancreatitis is more common in young age which is consistent with previous studies (Elzouki et al, 2019).In foregone studies, among the patients of idiopathic acute pancreatitis about 20-50% presented with microlithiasis (Liu et al, 2000;Ros et al, 1991;Dill & Dill, 2002;Lee & Nicholls, 1986;Levy, 2002) , 15% with chronic pancreatitis (Wilcox & Kilgore, 2009), 25% with common bile duct stone (Choudhary et al, 2016) and about 3.2% with pancreatic cancer (Tandon & Topazian, 2001). Our study almost resembled those previously found data.…”
Section: Discussionsupporting
confidence: 87%
“…Patients with operated gall bladder showed common bile duct stone (24.6%) and biliary ascariasis (21.4%) as the leading causes in our study. But Choudhary NS et al showed early chronic pancreatitis (38.6%) as the main cause of idiopathic acute pancreatitis in patients who underwent cholecystectomy (Choudhary et al, 2016). Khuroo MS and associates showed that biliary ascariasis is found in 23% of acute pancreatitis patients in South East Asia which is 21.4% in our study (Khuroo et al, 2016).…”
Section: Discussioncontrasting
confidence: 45%